Rural Marketing - Study of Consumer Behaviour with Reference to Hair Oils - Garg, Bhawna (Indian Journal of Marketing, 2007)
Rural markets are growing rapidly because of social, political and economical changes. Rural consumers are fundamentally different from their urban counter part. In present scenario hair oils is one of the many products, which is consumed by the rural consumer more than their counterpart. The rural consumers consume hair oils as essential goods. Many companies are marketing their hair oils under different brand names. This has made it essential to probe in to and analyse the impact of socio-economic influences in rural consumer behaviour in terms of their buying practices, brand loyalty and behaviour changes of rural consumers. In this study an attempt has been made to study the factors influencing the choice of the Brand of Hair oils in Jhangadi (Mawana).